Education and quality of employment in the main cities of Colombia (2011)
This paper analyses the quality of employment in the major cities of Colombia in 2009. 'The results show that, although the quality of employment has improved since 2001, it still continues to be below the necessary level of quality employment. It also demonstrates the endogenous nature of education and proposes a correcting procedure for obtaining consistent and efficient estimators of employment quality. In differentiating between salaried and self-employed workers, the results reveal that if an individual is self-employed, an increase in the number of years of education does not contribute to improving the quality of employment. This effect only occurs in the case of salaried workers.